(untitled) (Web of Teachers: Inderscience Research, 2024)
Studying the structure of a limit set is crucial for characterizing the long-term behavior and stability of a dynamical system. It is known that a bounded limit set is a continuum i.e. connected and compact, whereas unbounded ones may have enough complicated structure [1- 11]. For instance, the limit set of -system may consist of uncountable connectivity components. It can be shown that -limit set of quadratic systems is always connected. There is a cubic system on the plane which possesses the -limit set consisting of two straight lines. The limit set of a polynomial system on the plane may have connectivity components for arbitrary large [2]. In this paper we consider a problem how to construct a rational dynamical system with the -limit set consisting connectivity components.